Temporal and spatial changes of seagress distribution in Lawas, Sarawak, East Malaysia / Eda Izanie Ahmad Kamil - Eda Izanie , Ahmad Kamil (2013)
Seagrasses are flowering plants that have adapted to life under marine constraints. The term seagrass refers to the grass-like habit of most of its representatives (den Hartog & Kuo, 2006). Similar to the terrestrial grasses, seagrasses possess leafy shoots, rhizomes, roots, flowers and fruits. The leaves are distinct characteristic of the seagrass and can be use for species identification. It can vary in length, number of veins and shapes (such as spoon-like, ribbon-like, scythe-shaped or spinulose) depending on species (den Hartog, 1970; Lanyon, 1986; Japar Sidik et al., 1999; Phang, 2000; Gumpil & de Silva, 2007).